Communication Strategies Used By The Eighth Grade Students Of SMP N 1 Surakarta In Developing Speaking Skill - Herawati., Oktavia; , Mauly Halwat Hikmat, Ph. D.; , Aryati Prasetyarini, S.Pd, M.Pd (2015)
This research aims at identifying the type, the dominant type of communication strategies used by the eighth grade students of SMP N 1 Surakarta, and their function in developing speaking skill in the conversation. The data are the transcript of conversations which are made by the respondent in a speaking class. The data are taken by the researcher through observation, and recorded using tape recorder. They are analyzed by Tarone's theory of communication strategies. Triangulation is used to make credibility of the data. The researcher uses inter-rater reliability to establish the credibility of findings from an analysis. The findings of the research are: (1) the respondents use all the type of communication strategies, namely: a) topic avoidance, b) message abandonment, c) paraphrase, d) coinage, e) native language switching, f) miming and g) appeal for assistance, (2) the dominant type of communication strategies used by the respondents is native language switching with the percentage 35. 29%, and (3) the function of communication strategies type is to develop speaking skill through reaching communicative competence by using five types of communication strategies, namely: a) paraphrase, b) coinage, c) native language switching, d) miming and e) appeal for assistance.